Integrative systematics of the tarantulas Euathlus Ausserer, 1875 from Argentina: cladistics, molecular phylogeny and new species (Araneae: Theraphosidae) - Allegue, Maite (2025)
The present study contributes to the understanding of the diversity within the tarantula genus Euathlus Ausserer, 1875. Through a combination of cladistic, molecular, and morphological analyses, three new species are described: Euathlus basalticus sp. nov. from Neuquén, Euathlus kupal sp. nov. from Mendoza, and Euathlus susanae sp. nov. from the La Pampa-Mendoza provinces. Additionally, the female of Euathlus tenebrarum Ferretti, 2015 is described for the first time, revealing that the previously attributed female of this species belongs to E. basalticus sp. nov. Phylogenetic trees from both morphological and molecular datasets are presented. Preliminary molecular analyses reveal the identity and support the proposal of the species treated here. Morphological analyses found considerable diversity within Euathlus, particularly in genitalic structures, challenging the general assumption of morphological homogeneity among mygalomorph spiders. Cladistic analyses recovered the genus Phrixotrichus within Euathlus, though this hypothesis could not be tested with molecular data due to the lack of available sequences for Phrixotrichus. These results suggest that future taxonomic revisions may be complemented once molecular data become available. Altogether, our results provide new insights into the systematics and diversity of Euathlus and highlight the importance of integrative approaches for unraveling evolutionary relationships within this group.